Growth rate of Kappaphycus alvareziiby Rawai method in Saleh Bay, Tanjung Bele Hamlet, Sumbawa - handayani, fitry; Ahdiansyah, Yudi; Mardhia, Dwi; Bahri, Syamsul; Kautsari, Neri (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
The seaweed species Kappaphycus alvarezii has long been cultivated by the community in Tanjung Bele hamlet. The cultivation method they use is the longline method. Even though they have been cultivating seaweed for a long time, the development of seaweed in Tanjung Bele hamlet has not had a positive impact on the community's economy. Selecting the right and appropriate cultivation method will influence the success of seaweed cultivation.So this study aims to provide information on the growth rate of seaweed using the longline method used by the community in Tanjung Bele hamlet. The research method used a survey method with a planting period of 30 days. The initial weight of seaweed used was 200 g on 10 ropes. Seaweed growth observations were carried out 8 times. Descriptive data analysis. The research results showed that absolute growth ranged from 800 to 1000 g while the specific growth rate was in the range of 20 to 22%.